Squamous cell carcinoma of the head and neck – screening in patients who misuse alcohol and tobacco in Switzerland: a prospective pilot study. Issue 10 (December 2019) - Mermod, M.; Adam, A.; Clair, C.; Faouzi, M.; Simon, C.; Daeppen, J.-B.; Bertholet, N.; Monnier, Y.
Abstract: Squamous cell carcinoma (SCC) of the head and neck is the sixth most common cancer worldwide. It is preceded by early asymptomatic lesions which, if identified early enough and removed, would prevent malignant transformation or avoid delaying diagnosis to advanced stages. Our aim was to evaluate the feasibility of a screening programme for SCC of the head and neck in a group of high-risk patients, and to investigate their addiction profile. Patients admitted to an inpatient alcohol addiction centre (n = 101) were prospectively enrolled and asked to fill in a questionnaire about their use of tobacco and alcohol, and the presence of warning symptoms for SCC of the head and neck from 23 June 2014 to 21 January2016. Participants in the study had a physical examination by an alcohol addiction physician followed by a full examination of the head and neck by an otorhinolaryngologist to rule out premalignant or malignant lesions of the upper aerodigestive tract. Of the 101 patients, 62 (60%) had at least one warning symptom. Alcohol addiction physicians identified leukoplakia in six (6%) and erythroplakia in two. No pre-malignant or malignant lesions were confirmed on examination by the otolaryngologist. We were unable to draw conclusions about the cost-effectiveness or the yield of the screening programme. Despite our negative findings, we may need further investigation to clarify the relevance of such a programme on health-related outcome given the high compliance rate and minimal delay that was achieved by taking advantage of an in-patient alcohol rehabilitation centre.